A Theory of Costly Sequential Bidding. (19th April 2018) - Daniel, Kent D; Hirshleifer, David
Abstract: We model sequential bidding in a private value English auction when it is costly to submit or revise a bid. We show that, even when bid costs approach zero, bidding occurs in repeated jumps, consistent with certain types of natural auctions such as takeover contests. In contrast with most past models of bids as valuation signals, every bidder has the opportunity to signal and increase the bid by a jump. Jumps communicate bidders' information rapidly, leading to contests that are completed in a few bids. The model additionally predicts; informative delays in the start of bidding; that the probability of a second bid decreases in, and the jump increases in, the first bid; that objects are sold to the highest valuation bidder; and that revenue and efficiency relationships between different auctions hold asymptotically.